2013
DOI: 10.1093/brain/awt206
|View full text |Cite
|
Sign up to set email alerts
|

Plasma homocysteine, Alzheimer and cerebrovascular pathology: a population-based autopsy study

Abstract: Elevated plasma total homocysteine is associated with increased risk of dementia/Alzheimer's disease, but underlying pathophysiological mechanisms are not fully understood. This study investigated possible links between baseline homocysteine, and post-mortem neuropathological and magnetic resonance imaging findings up to 10 years later in the Vantaa 85+ population including people aged ≥85 years. Two hundred and sixty-five individuals had homocysteine and autopsy data, of which 103 had post-mortem brain magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
89
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 54 publications
9
89
1
Order By: Relevance
“…However, the effect of levodopa dosage was investigated in a mediation analysis which supports the hypothesis that elevated HC itself promotes cognitive decline in PD. This hypothesis is plausible in light of basic science evidence that elevated levels of HC are toxic to both neurons [23] and endothelial cells[24], and by clinical studies showing that elevated plasma HC predicts both neurofibrillary tangles and vascular pathology at brain autopsy [25], and that HC-lowering interventions slow cognitive decline in non-PD MCI patients[3] [4]. The hypothesis that HC is potentially harmful to PD patients is further supported by clinical studies showing that elevated HC predicts rate of brain atrophy in PD [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of levodopa dosage was investigated in a mediation analysis which supports the hypothesis that elevated HC itself promotes cognitive decline in PD. This hypothesis is plausible in light of basic science evidence that elevated levels of HC are toxic to both neurons [23] and endothelial cells[24], and by clinical studies showing that elevated plasma HC predicts both neurofibrillary tangles and vascular pathology at brain autopsy [25], and that HC-lowering interventions slow cognitive decline in non-PD MCI patients[3] [4]. The hypothesis that HC is potentially harmful to PD patients is further supported by clinical studies showing that elevated HC predicts rate of brain atrophy in PD [26].…”
Section: Discussionmentioning
confidence: 99%
“…An autopsy study showed a clear association between Hcy levels and neurofibrillary tangles, a known hallmark of AD, with an odds ratio of having such deposits of 2.60 (95% confidence interval 1.28–5.28) when comparing the top with the bottom Hcy quartile [138]. A prospective study showed greater brain atrophy in AD patients with higher Hcy levels [116] and this association between Hcy and grey matter atrophy has been confirmed by a range of studies (See review by Smith and Refsum [16]).…”
Section: Proposed Mechanisms Linking Polymorphisms Hcy B-vitaminmentioning
confidence: 99%
“…The association with hippocampal atrophy appears to be independent of amyloid pathology [14]. White matter lesions reflect vascular damage [92] and it is therefore notable that white matter changes are associated with HHCy [47,49,64,94] and with low vitamin B 12 levels [21] and low folate [51,100]. Evidence supporting a causal relationship between HHCy and cerebrovascular injury includes: i) independent, graded association of HHCy with stroke in prospective and retrospective clinical studies [48,61]; ii) genetic association studies of genes regulating HCy metabolism, using Mendelian randomisation [9]; iii) HHCy-induced lesions in experimental animals [4,68,108,111].…”
Section: Introductionmentioning
confidence: 99%